Internet of Things (IoT): BLYNK Framework for Smart Home - Media’s, E; ., Syufrijal; Rif’an, M (KnE Social Sciences, 2019)
This paper discusses the design to control and monitor devices at home via a smartphone. The purpose of this study is to make control and monitoring of electrical devices with the concept of IoT using Raspberry pi and NodeMCU based on the Blynk framework. The method used in this study is to build a prototype consisting of sensors, actuators, Raspberry pi, NodeMCU, and Smartphones. Actuators and Sensors are used to move device and the sensor is used to detect conditions. Raspberry pi is used as a server and as a bridge connected to the internet. The NodeMcu microcontroller is used as a link between equipment and sensors at home with the Raspberry pi. NodeMcu reads sensor data and sends it to the server. The server responds to requests for smartphones that have been installed by the Blynk framework. This system is designed to have an automatic mode when the homeowner is offline, and also has all the system log data. Keywords: IoT, Smart Home, Blynk